Rotor termination is critically dependent on kinetic properties of IKur inhibitors in an in silico model of chronic atrial fibrillation - Scholz, Eberhard P.; Carrillo-Bustamante, Paola; Fischer, Fathima; Wilhelms, Mathias; Zitron, Edgar; Dössel, Olaf; Katus, Hugo; Seemann, Gunnar (PLOS ONE, 2013)
Inhibition of the atrial ultra-rapid delayed rectifier potassium current (IKur) represents a promising therapeutic strategy in the therapy of atrial fibrillation. However, experimental and clinical data on the antiarrhythmic efficacy remain controversial. We tested the hypothesis that antiarrhythmic effects of IKur inhibitors are dependent on kinetic properties of channel blockade. A mathematical description of IKur blockade was introduced into Courtemanche-Ramirez-Nattel models of normal and remodeled atrial electrophysiology. Effects of five model compounds with different kinetic properties were analyzed. Although a reduction of dominant frequencies could be observed in two dimensional tissue simulations for all compounds, a reduction of spiral wave activity could be only be detected in two cases. We found that an increase of the percent area of refractory tissue due to a prolongation of the wavelength seems to be particularly important. By automatic tracking of spiral tip movement we find that increased refractoriness resulted in rotor extinction caused by an increased spiral-tip meandering. We show that antiarrhythmic effects of IKur inhibitors are dependent on kinetic properties of blockade. We find that an increase of the percent area of refractory tissue is the underlying mechanism for an increased spiral-tip meandering, resulting in the extinction of re-entrant circuits.
Gesehen am 15.07.2021
Im Titel ist "Kur" von IKur tiefgestellt